THE EFFECT OF USING ACTIVITY BOOK ON MASTERY OF KNOWLEDGE AND ATTITUDES ABOUT BALANCE NUTRITION FOR MADRASAH IBTIDAIYAH TARBIYATUL AULAD STUDENT IN NGUDIREJO VILLAGE JOMBANG DISTRICT - Afiah, Choirin Sayyidah; Sulandjari, Siti (Jurnal Gizi dan Kesehatan Nusantara, 2023)
AbstractActivity book is a book containing a series of skill activities and games for interactive learning activities. The activity book can be appIy as a medium to improve mastery of knowledge and attitudes about balanced nutrition in grade 3 students of madrasah ibtidaiyah. The purpose of this study was to decide the effect of using activity books on mastery of knowledge and attitudes about balanced nutrition in students of Madrasah Ibtidaiyah Tarbiyatul Aulad, Ngudirejo Village, Jombang Regency. Type of this research was quasi experimental. The research design was a non-equivalent control-group design, in which there were 2 groups: the experimental group which was given a balanced nutrition activity book and the control group which was given a balanced nutrition handout. The subjects in this study were 36 grade 3 students of Madrasah Ibtidaiyah, which consisted of 18 students in experimental group and 18 students in control group. The independent variable was the use of the Activity Book media, while the dependent variable in this study was mastery of balanced nutrition knowledge as measured with pretest and posttest, and balanced nutritional attitudes as measured with a questionnaire. Data analysis used the T test with a 95% confidence level. The results represented that nutrition education using activity book media had an effect on mastery of knowledge (p = 0.000) and attitudes (p = 0.001) in students of MI Tarbiyatul Aulad, Ngudirejo Village, Jomba Regency.Keywords: Activity Book, Balance Nutrition, Mastery of Knowledges and Attitudes, Nutrition Education